Co-created Technological Solutions for Caregivers in Health Care: Systematic Review - Jose Antonio Merchán-Baeza; Cristina Borralleras Andreu; Eduard Minobes-Molina; Sergi Grau Carrión; Montse Romero-Mas; Anna Ramon-Aribau (JMIR Publications, 2023)
BackgroundSupport interventions for caregivers can reduce their stress, possibly improving the quality of patients' care while reducing care costs. Technological solutions have been designed to cover their needs, but there are some challenges in making them truly functional for end users. Co-design approaches present important opportunities for engaging diverse populations to help ensure that technological solutions are inclusive and accessible. ObjectiveThis study aimed to identify co-created technological solutions, as well as the process followed for their co-creation, in the field of health for caregivers. MethodsThe literature review was conducted in the Medline, Web of Science, Scopus, Science Direct, Scielo, and IEEE Xplore databases. The inclusion criteria were studies written in English or Spanish and with a publication date until May 2021. The content had to specify that the caregivers actively participated in the co-creation process, which covered until the development phase of the technological solution (prototype). The level of evidence and the methodological quality were analyzed when possible, using the Scottish Intercollegiate Guidelines Network criteria and the Mixed Methods Appraisal Tool, version 2018, respectively. ResultsIn total, 410 papers were identified, and 11 met the eligibility criteria. The most predominant articles were mixed methods studies and qualitative studies. The technology used in the analyzed articles were mobile or web applications (9 studies) and specific devices such as sensors, cameras, or alarm systems (2 studies) to support the health and social aspects of caregivers and improve their education in care. The most common patient profile was older people (7 studies); 6 studies used co-creation in the requirements phase, 6 studies detailed the design phase. In 9 studies, the prototype was iteratively refined in the development phase, and the validation phase was performed in 5 of the reviewed studies. ConclusionsThis systematic review suggests that existing co-created technological solutions in the field of health for caregivers are mostly mobile or web applications to support caregivers' social health and well-being and improve their health knowledge when delivering care to patients, especially older people. As for the co-creation process, caregivers are particularly involved during development and in the design. The scarce literature found indicates that further research with higher methodological quality is needed.